Intra and interspecific morphological variations of three species of Capsicum (Solanaceae) - Resmi, L. (Current Botany, 2022)
The widely cultivated pepper, Capsicum spp., important as a vegetable and spice crop worldwide, is one of the most diverse crops. Considerable morphological variation, especially in fruit shape, color, and size exist in the genus. The present study analysed the intra and interspecific morphological variations of three species of Capsicum (Solanaceae) using thirty nine morphological characters. Morphological variations with respect to vegetative, floral and fruit characteristics were observed among the members of the same species. Morphological data was used to obtain UPGMA derived dendrogram and the cluster analysis indicated genetic divergence among the three species. Present observations imply a great potential for chilli breeding through a hybridization programme or direct use of the varieties for the successful production of promising cultivars.